2015
DOI: 10.1002/acr.22508
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Need for, and Use of Work Accommodations and Benefits: Are They Related to Employment Outcomes in People With Arthritis?

Abstract: ObjectiveTo examine the availability, need, and use of workplace policies for workers with osteoarthritis (OA) and inflammatory arthritis (IA) and their association with employment outcomes.MethodsParticipants (n = 219) were employed, ages ≥25 years, and diagnosed with OA or IA. They were recruited through community advertising and rheumatology clinics in 2 Canadian provinces. Respondents completed a 35–45‐minute telephone interview assessing demographics (age, sex), health (diagnosis, pain, activity limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 46 publications
5
61
0
Order By: Relevance
“…Participants were asked about 13 job accommodations (a combination of those commonly provided to employees in Canadian organizations and others found in the literature) (23,26,27,(35)(36)(37). Participants were asked whether each accommodation was needed (yes/no).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked about 13 job accommodations (a combination of those commonly provided to employees in Canadian organizations and others found in the literature) (23,26,27,(35)(36)(37). Participants were asked whether each accommodation was needed (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…These policies and laws are meant to reduce the impact of disabilities and potential employment disparities by eliminating barriers and helping persons with disabilities and chronic conditions gain access to employment and to manage job tasks (17). Some research among individuals with rheumatic diseases, such as systemic lupus erythematosus (SLE; lupus), has found that individuals who used job accommodations were more likely to remain employed (18)(19)(20)(21)(22)(23); had better performance evaluations, attendance, productivity, and safety records; and had lower turnover rates (24)(25)(26). However, studies also suggest that many individuals do not take advantage of job accommodations, despite having musculoskeletal conditions, including arthritis (23,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Over 60% of respondents stated they did not need the work at home arrangements (64.8%), which was also equal to the IBD patients included in this study. Among the osteoarthritis and inflammatory arthritis patients needing benefits or accommodations, many participants were able to use them, but overall this was more difficult in the accommodations requested by patients with IBD in this systematic review [11]. …”
Section: Discussionmentioning
confidence: 99%
“…To compare IBD to other chronic diseases, we looked at a study concerning the availability, need, and use of workplace adaptations of workers with osteoarthritis and inflammatory arthritis [11]. The accommodation most reported was special equipment and adaptations of the workplace, with most respondents receiving some form of accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation